(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Salsinha Y C F, Indradewa D, Purwestri Y A, Rachmawati D. 2020. Selection of drought-tolerant local rice cultivars from East Nusa Tenggara during vegetative stage. Biodiversitas 21: 170-178. East Nusa Tenggara (NTT), with the predominance of dry climate, has the potential of the plant with high tolerance to drought. This research was conducted to select drought-tolerant rice cultivars. There were eight NTT-rice cultivars tested: Pak morin (P1), Mapan (P2), Pak Mutin (P3), Gogo Fatuhao (P4), Seratus-malam Boawae (P5), Padi-Putih Kuatnana (P6), Padi-Putih Maumere (P7) and Gogo Sikka (P8) with 2 control cultivars tested: Ciherang (drought- susceptible) and IR-64 (drought tolerant). The treatment included were 100% FC (control), 50% FC (moderate) and 25% FC (severe drought) during vegetative stage. The morphological analysis of plant (plant height, number of leaves and tillers and root architecture) showed cultivars P1, P5 and P6 possess the best characteristics for tolerating drought. The physiological analysis (plant photosynthetic rate, stomatal conductance, intercellular CO2-concentration, and transpiration rate) showed cultivar P5 and P6 possess the best characteristics for tolerating drought. The high levels of chlorophyll and carotenoid contents during drought conditions were observed in P5, P6, and P7 cultivars. Based on the relative water content, membrane stability index and proline levels, highest-resistance cultivar was P5 and P7 while the cultivar with high sensitivity to drought stress was P3. Based on the morphophysiological characteristics, it can be concluded that P5, P6, and P7 cultivar have the potential as drought-tolerant rice.